Regional disparity of HIV incidence and prevalence among men who have sex with men - D. N. Vergara-Ortega; H. López-Gatell; S. Bautista-Arredondo; A. Colchero; S. G. Sosa-Rubí; M. Morales-Vazquez; A. Herrera-Ortiz; M. Olamendi-Portugal; S. García-Cisneros; E. E. Sevilla-Reyes; M. Hernández-Avila; M. A. Sánchez-Alemán (BMC Infectious Diseases, 2021)
Abstract Background HIV incidence can be estimated with cross-sectional studies using clinical, serological, and molecular data. Worldwide, HIV incidence data in only men who have sex with men (MSM) are scarce and principally focus on those with healthcare or under treatment. However, better estimates can be obtained through studies with national representativeness. The objective was to estimate the prevalence, incidence, and factors associated with acquiring HIV in a national sample of MSM who attend meeting places, considering geographical regions. Methods A nationally representative survey of MSM attending meeting places was performed in Mexico. Participants answered a questionnaire, and a dried blood spot (DBS) was collected. Samples were classified as recent infections using an algorithm with HIV status, antiretroviral therapy, and the result of BED-EIA assay. Parameters were analysed considering regions and demographic and sexual behaviour characteristics. Results The national HIV prevalence was 17.4% with regional differences; the highest prevalence (20.7%) was found in Mexico City, and the lowest prevalence was found in the West region (11.5%). The incidence was 9.4 per 100 p/y, with regional values from 6.2 to 13.2 for the Northeast and the Centre regions, respectively. Age, age at sexual debut, low wealth index, and rewarded sex were associated with HIV prevalence. Centre region, use of private clinics as health services, and having sex exclusively with men were associated with recent HIV infections. Conclusions The incidence and prevalence showed regional differences, suggesting a difference in the dynamics of HIV transmission; some regions have a greater case accumulation, and others have a greater rate of new infections. Understanding this dynamic will allow developing health programs focused on HIV prevention or treating people already living with HIV.